NEWS COVERAGE OF THE TORTURE SCANDAL OF DETAINEES AT ABU GHRAIB PRISON - Mahmoud Nafal, Nazhat (ALBAHITH ALALAMI, 2020)
According to the topics of study, The intensity of the news coverage of the Abu Ghraib scandal and the US soldiers’ torture of Iraqi prisoners have become apparent since the scandal was revealed on April 29, 2004 until May 30, 2004 and the period in which the coverage of this scandal had intensified not only in Al-Zaman, but in all newspapers, magazines and other media locally and internationally. And according to a research taken from Al-Zaman magazine that showed great interest in highlighting the event, interpreting it, following up its roots and results, and showing contradictory claims and slogans between the US and Britain, particularly in respecting human rights and the spread of justice, equality and well-being in Iraq specifically and what happened actually from violations and abuses of US forces, and whoever made an alliance with them against the Iraqi people which are contrary to all international laws, legislations and conventions that prevent the violation of human dignity in times of peace and war alike and can not be accepted under any justification. The importance of the news reports was also revealed in the dissemination of the essence of the event and its reasons, and based on new factual information in a clear and simple manner, and a comprehensive explanation of most aspects of the event and all relevant developments, ideas, attitudes and results. For more honest and objective follow-up, the reports relied on documents supporting the information since the beginning of the event, and highlighted the US abuses and violations of international laws and the resolutions of the Security Council and the United Nations in the violation of human rights, and that was proved by the (categories of analysis) which highlighted the obvious contradiction between the slogans and behaviors and practices, this was obtained with the adoption of specific scientific steps. After the analysis of the news reports of the newspaper Al-Zaman, it showed many results focusing on highlighting the condemnation and anger of the Iraqi people against the crimes of torture in Abu Ghraib prison, whereas the US officials’ stated that the US administration’s justice will punish the American soldiers for Abusing the Iraqi prisoners, also highlighting the heinous torture and humiliation of US soldiers against prisoners. The Red Cross, The Unicef and Amnesty International were also concerned about the need to punish the perpetrators of torture crimes. The focus was also on the US president’s claim to insist on peace and security in Iraq. Iraqi and international claims blamed the American minister of defense Donald Ramsfield, for the torture crimes against Iraqi prisoners. This scandal led to the escalation of international and US hostility against Washington and It showed how clear the British claims were contradictory in the analysis which questions the validity of the abuse of British soldiers against the Iraqi detainees.